PENGARUH ENVIRONMENTAL, SOCIAL, AND GOVERNANCE TERHADAP VOLATILITAS HARGA SAHAM DALAM PERIODE PANDEMI COVID-19 DENGAN EFFECTIVE TAX RATE SEBAGAI VARIABEL MODERASI - Siswana, Feky Henry; Ratmono, Dwi (Diponegoro Journal of Accounting, 2024)
This study aims to examine the effect of environmental, social, and governance (ESG) disclosure on stock price volatility and how effective tax rate moderates this relationship during the Covid-19 pandemic period. Variables used in the examination are environmental, social, and governance disclosure as independent variable, stock price volatility as dependent variable, and effective tax rate as moderating variable.In this study, a total of 123 samples were taken from companies that are part of the ESG Quality 45 IDX KEHATI Index. The samples were chosen using a purposive sampling method. The statistical technique used in this research is multiple linear regression analysis, moderated regression analysis (MRA), absolute difference moderation, residual-based moderation, and sensitivity analysis.The result of this study shows that environmental, social, and governance disclosure has a negative effect on stock price volatility. Meanwhile, effective tax rate doesn't weaken the negative impact of ESG disclosure on stock price volatility.